Eco-friendly synthesis of porous and charged polyethersulfone membrane for improved protein separation efficiency - Talukder, Md Eman; Pervez, Md. Nahid; Song, Hongchen; Buonerba, Antonio; Stylios, George K.; Naddeo, Vincenzo; Kujawski, Wojciech; Figoli, Alberto (Results in engineering, 2025)
•A new sustainable honeycomb-structured PES-PVA porous membrane was synthesized.•Increased surface charge and hydrophilicity were responsible for improving protein separation.•BSA formed an electrostatic bond with PES/PVA, leading to a synergistic effect in fouling.•The water flux and protein rejection rates (99%) were higher for the PES-PVA membrane.•Polarclean® was used as a solvent for fabricating PES/PVA membranes. This research article aims to develop a novel, sustainable, porous charged membrane with excellent antifouling performance. It focuses on creating a porous polyethersulfone/ polyvinyl alcohol (PES-PVA) negative charged membrane with a porous surface structure, employing polyvinylpyrrolidone (PVP) and a green solvent (PolarClean) to improve the wettability of the membrane. The characteristics of the composite membranes, such as morphology, mechanical properties, porosity, pore size, and water permeability, were scrutinized. The PES-PVP blended membrane exhibited a significantly higher water flux of 542.2 ± 5.4 L m−2 h−1 bar−1 relative to the pure PES membrane, which had a flux of 289.4 ± 3.4 L m−2 h−1 bar−1. PEG molecular weight cut-offs (MWCOs) and rejection rates were 50 - 500 kDa and 89 - 99 %, respectively. BSA is repulsed to the PES/PVA membrane surface, which highly rejects proteins. Additionally, using lower molecular weight and PVA concentration could yield membranes with increased protein flux and enhanced protein rejection (99 %) along with strong fouling resistance (99.9 %), surpassing the performance of blended PES membranes and other commercial membranes (CMs).